Pengaruh Rasio Keuangan Terhadap Profitabilitas Pada Bank Umum Syariah di Indonesia Periode 2017-2021 - M. Faza Ardichy; Yayuk Sri Rahayu (Owner : Riset dan Jurnal Akuntansi, 2022)
The research was conducted with the aim of examining the effect of financial ratios on profitability in Islamic commercial banks registered with the financial services authority of the Republic of Indonesia. This study was tested with four independent variables, namely Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Efficiency Ratio (OER), and Financing to Deposit Ratio (FDR). While the dependent variable is Return on Assets (ROA). This study uses research samples published in the financial services authority of the republic of Indonesia with quarterly data for the period 2017-2021. While the data technique in this study used panel data regression analysis. Based on the results of the partial analysis, first, the Capital Adequacy Ratio has a negative and significant effect on Return on Assets. Second, Non-Performing Financing has a negative and significant effect on Return on Assets. Third, the Operational Efficiency Ratio has a negative and significant effect on Return on Assets. Fourth, the Financing to Deposit Ratio has a negative and significant effect on Return on Assets. Meanwhile, simultaneously CAR, NPF, OER, and FDR have a significant effect on ROA. The coefficient of determination (R square value) is 0.9650, this means that 96.50% of the variation of the dependent variable ROA is explained by the variation of the independent variables, namely CAR, NPF, OER, and FDR. While the remaining 3.50% (100% - 96.50% = 3.50%) get the influence of variables that are not in the study.